Prevalence and Outcomes of Hepatitis B Coinfection and Associated Liver Disease Among Antiretroviral Therapy-Naive Individuals in a Rural Tanzanian Human Immunodeficiency Virus Cohort. (29th July 2016) - Ramírez-Mena, Adrià; Glass, Tracy R.; Winter, Annja; Kimera, Namvua; Ntamatungiro, Alex; Hatz, Christoph; Tanner, Marcel; Battegay, Manuel; Furrer, Hansjakob; Wandeler, Gilles; Letang, Emilio; ,; et al.
Abstract : Key findings include a high prevalence of APRI score indicating significant fibrosis/cirrhosis in ART-naïve individuals particularly among HIV/HBV-co-infected individuals and a regression of APRI to <1.5 after 12-24 months of ART in the majority of participants with APRI score indicating significant fibrosis, irrespective of HBV status. Abstract: Background. We evaluated the prevalence of chronic hepatitis B virus (HBV) infection and liver fibrosis/cirrhosis in human immunodeficiency virus (HIV)-infected individuals enrolled in a rural Tanzanian prospective cohort and assessed hepatic fibrosis progression 12–24 months after antiretroviral treatment (ART) initiation. Methods. All ART-naive HIV-infected adults ≥15-year-old enrolled in the Kilombero and Ulanga Antiretroviral Cohort who started ART between 2005 and 2015 were included. Pre-ART factors associated with significant liver fibrosis (aspartate aminotransferase-to-platelet ratio index [APRI] >1.5) and cirrhosis (APRI > 2.0) were identified using logistic regression. Results. Of 3097 individuals screened, 227 (7.3%; 95% CI, 6.4–8.2) were hepatitis B surface antigen (HBsAg) positive. Before ART initiation, 9.1% individuals had significant liver fibrosis and 5.3% had cirrhosis. Human immunodeficiency virus/HBV-coinfected individuals were more likely to have an APRI score indicating significant fibrosis (14.2% vs 8.7%, P = .03) and cirrhosis (9.2% vs 4.9%, P = .03) than HBV-uninfected patients. CD4 cell count <200 cell/μL and alcohol consumption were independently associated with pre-ART APRI score, indicating significant fibrosis and cirrhosis in multivariable analyses. Among individuals with elevated APRI measurements pre- and 12–24 months post-ART initiation, 53 of 57 (93.0%) of HIV-monoinfected and 4 of 5 (80.0%) of HIV/HBV-coinfected had a regression to APRI < 1.5. Conclusions. Hepatic fibrosis and cirrhosis were common in our cohort, especially among HIV/HBV-coinfected individuals. The APRI improved in most patients. Pre-ART HBsAg screening and early onset of tenofovir-based ART for HIV/HBV-coinfection should be prioritized in sub-Saharan Africa.